Lviv Classical Archaeology Before World War II - Natalia Bulyk; Roman Berest; Olena Tomeniuk (Archaeologia Polona)
At the end of the 19th and the beginning of the 20th centuries, Europe experienced a period of scientific advances in various fields. This is associated with the results of numerous surveys, discoveries, accidental finds, and scientific research, contributing to the appearance of scientific societies and new disciplines. In the field of history, the incredibly rich but little-known ancient architectural, archaeological, and written heritage attracted the attention of many researchers. This resulted in the collection of ancient antiquities, gradually forming a whole direction of scientific research – classical archaeology. The Department of Classical Archaeology and Prehistory of Lviv University (1905) became the main centre of the development of classical archaeology in Eastern Galicia (Eastern Halychyna, now – western Ukraine). The first classical archaeologist from Lviv was Professor Karol Hadaczek. After his tragic death and the beginning of World War I, the Department of Classical Archaeology and Prehistory was divided into two independent departments. Classical archaeology was headed by Edmund Bulanda, with whom the entire development of interwar Lviv classical archaeology is inseparably linked. E. Bulanda’s greatest legacy was his students (K. Michałowski, K. Majewski, I. Starchuk, E. Kulczycki), who, after the war, led entire areas of scientific research in Polish universities and made a significant contribution to the study and increasing public awareness of the classical heritage.